Nuttalliellidae in Burmese amber: implications for tick evolution - Lidia Chitimia-Dobler; Stephan Handschuh; Jason A. Dunlop; Ronel Pienaar; Ben J. Mans; Ala Tabor (Parasitology)
Ticks are composed of 3 extant families (Argasidae, Ixodidae and Nuttalliellidae) and 2 extinct families (Deinocrotonidae and Khimairidae). The Nuttalliellidae possess one extant species (Nuttalliella namaqua) limited to the Afrotropic region. A basal relationship to the hard and soft tick families and its limited distribution suggested an origin for ticks in the Afrotropics. The Deinocrotonidae has been found in Burmese amber from Myanmar and Iberian amber from Spain, suggesting a wider distribution of the lineage composed of Deinocrotonidae and Nuttalliellidae. The current study describes 8 fossils from mid-Cretaceous (ca. 100 Ma) Burmese amber: 2 Deinocroton species (Deinocroton bicornis sp. nov.; Deinocroton lacrimus sp. nov.), 5 Nuttalliella species (Nuttalliella gratae sp. nov., Nuttalliella tuberculata sp. nov., Nuttalliella placaventrala sp. nov., Nuttalliella odyssea sp. nov., Nuttalliella tropicasylvae sp. nov.) and a new genus and species (Legionaris nov. gen., Legionaris robustus sp. nov.). The argument is advanced that Deinocroton do not warrant its own family, but forms part of the Nuttalliellidae comprising 3 genera, Deinocroton, Legionaris nov. gen. and Nuttalliella). Affinities of Burmese tick fossils to the Australasian region, specifically related to rifting of the Burma terrane from northern Australia ~150 million years ago, suggest that Nuttalliella had a much wider distribution than its current limited distribution. The distribution of Nuttalliella likely stretched from Africa over Antarctica and much of Australia, suggesting that extant members of this family may still be found in Australia. Considerations for the geographic origins of ticks conclude that an Afrotropic origin can as yet not be discarded.